Optimization Design of New Bionic Propeller - WU Chunxiao, LU Yu, LIU Shewen, GU Zhuhao, SHAO Siyu, SHAO Wu, LI Chuang (Shanghai Jiaotong Daxue xuebao, 2023)
A novel method for optimal design of hydrodynamic performance of bionic propeller with a deformable leading edge is proposed. Based on the bionics principle and method of parameterized modeling, the fore-fin concave-convex structure of humpback whales is applied to the propeller leading edge, the leading edge in the propeller to meet flow region according to the exponential decay curve and the standard sine curve smooth leading edge for similar humpback fins protuberant structure of concave and convex deformation, and the leading edge of concave and convex bionic propeller. The hydrodynamic performance, the cavitation performance, and the noise performance of the exponential decay bionic propeller and the sinusoidal function bionic propeller were simulated respectively. The propeller with a better performance is selected, and the simulation based design (SBD) technology is introduced into the optimization design of the new bionic propeller. The parameters controlling the shape of the exponential attenuation curve of the guide edge deformation are taken as optimization design variables, the torque of the parent propeller is taken as the constraint condition, the open water efficiency is selected as the objective function, and the optimization algorithm of Sobol and T-Search is adopted. A bionic propeller optimization system based on the exponential decay curve is constructed. The results show that the application of the concave and convex structure of the humpback whale fore-fin to the guide edge of the propeller improves the cavitation performance and noise performance of the propeller, but the improvement of the open water performance of the propeller is not particularly significant. It is verified that the hydrodynamic performance optimization design method of the bionic propeller established in this paper is effective and reliable, which provides a certain theoretical basis and technical guidance for the performance numerical calculation and configuration optimization design of the bionic propeller.